دراسة لواقع حال المدى المعرفي للتربیة الكشفیة لمدرسي ومدرسات الاختصاصات الغیر ریاضیة في مدارس المتوسط والاعدادي والثانوي محافظة بغداد / الكرخ 3 - هبة احمد عبد الجبار (الرياضة المعاصرة)
The Scout movement is a behavioral & Social movement that meant to Build & Guide The Youth Generations to the Righteous Path & prevent it from Degradation , to prepare it to A Better Future & A Bright Tomorrow ware The Ethics & Manners of the individual have the Ultimate Priority. Thus we can Consider The Scout movement AS Fulfillment For Scholar Curriculum that can blog the un Prevented Gaps in the Normal Schools Curriculum . & in one word it is a behavioral Raisin Prepare the individual to the public Active life by Relying on Nature , & that what Maked The Searcher to Conduct A study About A Factual Study for the Knowledge Range About The Principles of The Scout Behevrisom for The Teachers In Mid School , Junior high & High School For Male & Female Schools . Aims of Research:- TO Gain the Knowledge Range About The Principles of The Scout Behevrisom for The Teachers In Mid School , Junior high & High School For Male & Female Schools .& The Have Searcher Concluded There is A Great Deal of Seclusion by the Teachers of Humane & Scientific Specialties by ignoring the teachings & principals Scout Movement & its Practice , Thus They own a The Knowledge Culture of the Significance of The Scout Behevrisom & movement & its Influential Effect in Improving the Scientific Side for the Students. The searcher Have Used the Discretional Method by Survey Style that fits the Nature of the study . Research Specimen :- It was "350" Teachers of both Genders Distributed In Mid School , Junior high & High School For Male & Female Schools In Baghdad Governorate \ 3RD Karkh District . & the results was Processed by the proper Spastically Methods to acquire the Knowledge Range of the Scout Behevrisom for the non Athletic Teachers " Both Genders " by the Questioner Form the was Prepared By The Researcher & Consistent of one Axis that is the Knowledge Axis of Scout Behevrisom